(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This study has been conductedwith the sociological approach. Therefore, it is desirable that we brieflyexplain what this approach is. Sociology was fathered by the French philosopherAuguste Comse. It has greatly changed, matured and become multi-faceted in itsapproach during the last 172 years and more so in the last 50 years. In thebeginning it was having, by and large, the most popular Social Survey method.Then in the later decades of the 19th Century and the beginning decades of the20th Century, Historical, Comparative and Ideal-Type Analysis and moresophisticated Social Survey and Statistical approaches as well as the Empiricalor Field Work approach of the Social Anthropologists like Malinowski, MargaretMead, Raymond Firth, M.N. Srinivas and S.C. Dube et al became the most commonsociological approaches.